Character Development Through Conflict: Alice’s Struggle for Selfhood in Alice’s Adventures in Wonderland - Devi Rahmawati; Gurendi Wiwoho (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This thesis examines the character development of Alice through the conflicts she faces in Lewis Carroll’s novel Alice’s Adventures in Wonderland (1865). The source of data used in this study is the 10th edition of the novel published by Gramedia. This study focuses on the internal and external conflicts experienced by Alice as the main character in Wonderland. The writer applies a qualitative descriptive method and uses four theories to analyze the conflicts encountered by Alice. The findings show that Alice is a round character who develops throughout the story as a result of the conflicts she experiences. The external conflicts include man versus person and man versus society. These conflicts contribute significantly to Alice’s emotional and personal growth. Wonderland becomes a place where Alice learns to leave behind her former self and adapt to unfamiliar situations and rules. Throughout her journey, Alice transforms from a timid child who is afraid to express herself into a brave and confident individual. This study concludes that conflicts in Alice’s Adventures in Wonderland function not only as plot elements but also as important factors in shaping Alice’s selfhood.